Letter from Chairman of Press Committee, General Council to Robert Williams, Victoria House Printing Co, 5 May 1926, re: printing of British Worker
1926-05-05 "Letter from Chairman of Press Committee, General Council to Robert Williams, Victoria House Printing Co, 5 May 1926, re: printing of British Worker" [g0728001.jpg], 5 May 1926, Williams, Robert TUC Organisation